1982
DOI: 10.1111/j.1744-313x.1982.tb00988.x
|View full text |Cite
|
Sign up to set email alerts
|

Another Example of Haemopoietic (Twin) Chimaerism in a Subject Unaware of Being a Twin

Abstract: SUMMARY A fourth human blood group chimaera studied in Birmingham is an example of haemopoietic (twin) chimaerism in which the subject was unaware of being a twin. Chimarerism was discovered during routine antenatal serological investigation in which it was shown that the proposita has two red cell populations, one of the rhesus genotype rr, and the other R1r. Further studies showed that she has two populations of lymphocytes, one with the female karyotye, 46XX, and the other with the male karyotype, 46XY. Ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Bird et al [9] recorded a suggestion that, because the yolk sac is one ofthe earliest sites of haemopoiesis, fusion of the primitive cir culations of two yolk sacs could lead to for mation of a twin chimera with no apparent twin. However, Lassila et al [42] using chick-chick embryos distinguished by differ ent B locus antigens showed that, although yolk sac stem cells are responsible for prim itive erythrocytes, embryonic stem cells are the only progenitors of lymphocytes and permanent red cells.…”
Section: Determination Of Typementioning
confidence: 99%
See 2 more Smart Citations
“…Bird et al [9] recorded a suggestion that, because the yolk sac is one ofthe earliest sites of haemopoiesis, fusion of the primitive cir culations of two yolk sacs could lead to for mation of a twin chimera with no apparent twin. However, Lassila et al [42] using chick-chick embryos distinguished by differ ent B locus antigens showed that, although yolk sac stem cells are responsible for prim itive erythrocytes, embryonic stem cells are the only progenitors of lymphocytes and permanent red cells.…”
Section: Determination Of Typementioning
confidence: 99%
“…P.M. [62,No.20 in table 92], and a new one, Mrs. C. C. [9], with no known twin are not included in this sec tion, but will be discussed below in the sec…”
Section: Twin Chimerasmentioning
confidence: 99%
See 1 more Smart Citation
“…20 in table 921, and a new one, Mrs. C.C. [9], with no known twin are not included in this section, but will be discussed below in the sec-tion on chimeras of unknown type (see Appendix 3). Ascertainment 27 ofthe 32 propositi were found through two populations of red cells.…”
Section: Twin Chimerasmentioning
confidence: 99%
“…Known reasons for such findings include hematopoietic or whole-body chimerism (presence of cells from 2 or more zygotes), mosaicism (presence of cells of different phenotypes derived from one zygote), and somatic RHD mutation. [4][5][6][7] Recently, also mosaicism involving a cell line with uniparental isodisomy for chromosome 1 was described as a reason for ambiguous RhD typing. 8 Many individuals with spontaneous Rh phenotype splitting or progressive Rh antigen loss were found to suffer from hematologic disease, such as acute or chronic myelogenous leukemia, myeloproliferative disease, or myelodysplastic syndrome, in the majority of cases without detectable cytogenetic abnormalities of chromosome 1.…”
Section: Introductionmentioning
confidence: 99%